2014
DOI: 10.7314/apjcp.2014.15.15.6443
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Stimulated Thyroglobulin Level as a Good Predictor of Successful Ablation after Adjuvant Radioiodine Treatment for Differentiated Thyroid Cancers

Abstract: Background: To determine the predictive value of the baseline stimulated thyroglobulin (STg) level for ablation outcome in patients undergoing adjuvant remnant radioiodine ablation (RRA) for differentiated thyroid carcinoma (DTC). Materials and Methods: This retrospective study accrued 64 patients (23 male and 41 female; mean age of 40±14 years) who had total thyroidectomy followed by RRA for DTC from January 2012 till April 2014. Patients with positive anti-Tg antibodies and distant metastasis on post-ablativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Absence of residual thyroid tissue is extremely rare even after successful total thyroidectomy applied by experienced surgeons. In patients with total thyroidectomy followed by I-131 ablation for DTC, the baseline stimulated-Tg level is a good predictor of successful ablation (12). In the literature, some studies have reported that the serum Tg/serum TSH ratio was an important predictor of ablation success that correlated well with patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Absence of residual thyroid tissue is extremely rare even after successful total thyroidectomy applied by experienced surgeons. In patients with total thyroidectomy followed by I-131 ablation for DTC, the baseline stimulated-Tg level is a good predictor of successful ablation (12). In the literature, some studies have reported that the serum Tg/serum TSH ratio was an important predictor of ablation success that correlated well with patient outcomes.…”
Section: Discussionmentioning
confidence: 99%